The Influence of Religious Character, Confident Character, and Responsible Character on the Entrepreneurial Interests of Students at State Elementary School 17 Bajoe, Bone Regency - W, Muhamaad Fahreza; M, Ahmad Aswar; Yunus, Muh.; Ebabu, Abrihan; W, Allan Gibb (Al-Hijr: Journal of Adulearn World, 2022)
This study aims, (1). Analyzing the Influence of Religious Character on Students' Interest in Entrepreneurship at SD Negeri 17 Bajoe, Bone Regency. (2) Analyzing the influence of the Confident Character on the Entrepreneurial Interest of Students at SD Negeri 17 Bajoe, Bone Regency, (3). Analyzing the Effect of Responsible Character on Entrepreneurial Interest of Students at SD Negeri 17 Bajoe, Bone Regency. This research was conducted at SD Negeri 17 Bajoe, Bone Regency with a total population and teacher sample of 90 students from grades 4, 5, and 6. This type of research was quantitative with a partial least squares (SEM-PLS) structural model approach. In this study, data were obtained from documentation, interviews and questionnaires. The results showed that (1) religious character had a positive and significant effect on the entrepreneurial interest of students at SD Negeri 17 Bajoe, Bone Regency. where the t-statistics value is greater than 1.96, (2) the character of self-confidence has a positive but not significant effect on the Entrepreneurial Interest of Students at SD Negeri 17 Bajoe, Bone Regency, as shown in table 4.13 where the t-statistics value is smaller than 1, 96, (3). The character of responsibility has a positive and significant effect on the Entrepreneurial Interest of Students at SD Negeri 17 Bajoe, Bone Regency, where the t-statistic value is greater than 1.96..